Mad Narcissists — The Myth of Narcissus in American Psycho and Mythological Revisionism in the Manosphere - Jaime SEGURA SAN MIGUEL (HyperCultura, 2024)
Identity, often conceptualized as a continuum of the ego, lies at the conflux of both individual and collective interpretations of reality. The constructions of reality and identity are, however, far from being a purely cognitive trait; both are constructed through interaction with others, to the point where faulty interactions can lead to a lack of individuation, and the echo chambers of the Manosphere can skew a subject’s interpretation of reality. The postmodern turn of cinema after the 1980s, acknowledging this relativism, presented deeply pathological characters in a more nuanced way, giving way to ambiguity. Bret Easton Ellis’s American Psycho’s Patrick Bateman is a pathological character who is described as having pathological traits but who has nonetheless been adopted by the Manosphere as an idealized role model. This article aims to comment on the mythical subversion of the myth of Narcissus in the narrative, the identity problem that Patrick Bateman suffers from, and to disentangle the processes whereby the Manosphere is misappropriating classical myths, mythologizing narrative characters to phenomenologically construct a different perception of reality, and how these problems are linked with an unrealized identity.